PENERAPAN TEKNOLOGI MESIN PEMARUT GULA MERAH VARIAN RASA JAHE : THE APPLICATION OF BROWN SUGAR GRATER MACHINE TECHNOLOGY FOR GINGER FLAVOURED VARIANT - Bahtiar, Ahmad Dony; Hendarti, Devina Rosa; Arif, Saiful; Nur Hamidah, Fitria; Mubarok, Ahsin Fahmi (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
Brown sugar is one of the natural sweeteners in the community. Where the sale of brown sugar has fluctuated due to the constant demand for brown sugar. Researchers aim to increase productivity and increase interest in brown sugar, so a new product is made, namely brown sugar with a ginger flavor. Therefore, the researchers made a ginger- flavoured brown sugar machine as a souvenir drink typical of the city of Kediri with a capacity of 150 liters/hour. the method used is a design method, which includes the planning stage, calculation, manufacture or assembly, and testing the machine. Which in this section explain more on the transmission system, which cover electric. In the results of the report above, it can be concluded that the planning for the number of scar teeth obtained a cylinder length of 90 mm and a cylinder diameter of 50 mm and the distance between the teeth of the scar 1 and the teeth of the scar 2 is 3 mm and the number of teeth planned for scarring is 840 teeth of the scar. The correction factor has a value of 0.186 kW. In machine testing, the comparison results obtained that 20 liters of brown sugar requires 1.134 kg of ginger and the grating process takes 13 minutes. Using an electric motor as a power source with a size of 1/4 HP, 220 volts, 200 watts and a speed of 2800 rpm. The quality of the grated ginger produced is very soft motor dynamo, grater eye, grater cover, fiter